Political economics in health and implications for neurosurgery diseases - Han, Yi; Huang, Yutao (Frontiers in Public Health, 2025)
The field of political economics in health has a significant and far-reaching impact on public health. It encompasses a diverse range of interconnected domains, including the economy, welfare, the environment, food and drug safety, pollution emissions, occupational safety, the quality of medical services, consumer rights, public health policy, healthcare policy, scientific research, and marketing management. In this review, we examine the global influence of political economics on health outcomes and delineate the impact of prevalent neurosurgical conditions on individual and collective healthcare resources. This review will discuss the effects of political-economic factors on the prevalence and treatment of neurosurgical diseases, including stroke, traumatic brain injury (TBI), intracerebral hemorrhage (ICH), and brain malignant tumors. Furthermore, the current challenges and future directions will be discussed. We intend this review to facilitate the exchange and integration of political economics, public health, and neurosurgery, provide a foundation for policy development, enhance the prevention, diagnosis, and treatment of neurosurgical diseases, and ultimately promote public health.